The Effect of Inclusion Style Using Electronic Device On Learning Front and Side Movement in Squash For Beginners Aged 13 – 15 Years Old - Jibad, Ali; Hassan, Ali (Journal of Physical Education, 2019)
The problem of the research lies in learning basic skills using traditional methods takes longer time thus the importance of the research was in using modern electronic devices to help beginners learn front and side movement in squash. The researchers used the experimental method on subjects of (6) beginner squash players aged 13 – 15 years old. The results showed statistical differences between pre and posttests in favor of posttests and that the exercises have a positive effect on developing the level of learning front and side movement in squash players.